Penguatan Pendidikan Karakter Berbasis Multikultural melalui Mata Pelajaran PKn - Bakar, Abu (Al-Mafahim: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This study aims to analyze the strengthening of multicultural-based character education through Civics (PKn) subjects in Islamic Elementary Schools (MI) by employing a qualitative library research method. The research subjects consist of academic literature, including books, journals, and policy documents, while the object of study focuses on the integration of multicultural values in the PKn curriculum at the MI level. Data were collected through systematic searches in academic databases using keywords such as "character education," "multiculturalism," and "civic education," followed by content analysis to identify themes and theoretical gaps. The findings indicate that PKn has significant potential to foster multicultural character values when contextual and active learning approaches are applied. However, challenges such as teachers' limited understanding of multicultural pedagogy and a lack of localized teaching materials hinder optimal implementation. The study concludes that strengthening multicultural character education in MI requires curriculum development, teacher training, and community collaboration to enhance students' tolerance, empathy, and national awareness.